PERSPEKTIF HUKUM PIDANA TERHADAP PERILAKU CATCALLING DI SOSIAL MEDIA - Alriansyah Sakhi Fauzan; Diana Lukitasari; Winarno Budyatmodjo (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2022)
This study examines the perspective of criminal law related to the problem of verbal sexual harassment or catcalling, with advances in information and communication technology, crime has now progressed rapidly, not to mention the crime of verbal sexual harassment or catcalling which is carried out on social media, perpetrators of harassment This verbal sexual activity uses social media to carry out its actions, by way of comments or uploading content that contains elements of catcalling, currently catcalling is still considered only a joke, the act of catcalling has violated the norms of decency and morality. In this journal the author discusses how to apply criminal law regarding verbal sexual harassment or catcalling behavior and discusses how the perpetrators of catcalling behavior can be subject to criminal sanctions in accordance with applicable law in Indonesia. Number 44 of 2008 concerning Pornography, Law Number 19 of 2016 concerning Information and Electronic Transactions, Law Number 12 of 2022 concerning Crimes of Sexual Violence. In this paper, the author uses normative research methods and analyzed using syllogistic analysis techniques with deductive thinking patterns.